Fourth Industrial Revolution and higher education in Peru - Anchante Arias, Jim Alexander (2023)
This article seeks to reflect on the problems of the Fourth Industrial Revolution in relation to higher education in Peru. To do this, first the concept of Education 4.0 is analized, which has been increasingly disseminated in the current scientific literature. Below, a set of ideas is established around the situation of higher education in our country during the context of the pandemic. Finally, it reports on a series of activities that some institutions, both universities and technological institutes, have been developing with the aim of spreading the reach of 4RI in Peruvian education.